Predictive value of different baseline optical coherence tomography biomarkers for visual acuity changes in neovascular age-related macular degeneration - Hamid Riazi-Esfahani; Hooshang Faghihi; Fatemeh Bazvand; Mohammadreza Mehrabi Bahar; Hassan Khojasteh; Ahmed Husein Ahmed; Shahin Faghihi; Ali Fakhraie; Mohammad Hossein Zamani; Samin Ghasemi; Esmaeil Asadi Khameneh; Elias Khalili Pour (International Journal of Retina and Vitreous)
Abstract Background To evaluate baseline optical coherence tomography (OCT) biomarkers in treatment-naïve patients with neovascular age-related macular degeneration (nAMD) and their correlation with visual acuity changes following intravitreal aflibercept injections. Methods A retrospective analysis was conducted on treatment-naïve nAMD patients. Baseline OCT biomarkers, including shallow irregular pigment epithelial detachment (SIPED), subretinal hyperreflective material, subretinal fluid, intraretinal fluid (IRF), hyperreflective foci, and subretinal drusenoid deposits, were assessed. Patients received bimonthly aflibercept injections after three loading doses. Visual acuity changes were evaluated at 3 and 12 months. The maximum height and width of the largest pigment epithelial detachment (PED) were also measured. Results Among 89 eyes with nAMD, mean best-corrected visual acuity (BCVA) improved by 6 Early Treatment Diabetic Retinopathy Study (ETDRS) letters from baseline to month 3, with sustained improvement through month 12. Baseline IRF was associated with poorer visual acuity improvement at month 12, with patients showing a mean improvement of 1.6 ± 18.2 ETDRS letters versus 11.1 ± 10 ETDRS letters in those without IRF (P = 0.002). Multivariable analysis indicated SIPED was linked to lower visual gains at month 3 (P = 0.025). The largest PED width correlated significantly with lower BCVA gains at months 3 (P = 0.021) and 12 (P = 0.043), suggesting its potential as a prognostic factor. Conclusion Baseline OCT biomarkers, including SIPED, IRF, and PED width, may predict visual acuity changes in nAMD patients treated with aflibercept, highlighting the need for individualized monitoring. Clinical trial number Not applicable.